Analisa Penerapan Perhitungan Rekonsoliasi Fiskal Terhadap Laporan Keuangan Komersial - Deddy Dariansyah (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
The calculation of fiscal reconciliation made by the company (taxpayer) due to differences in calculations, especially profit by commercial accounting and taxable profit (fiscal). to bridge the existence of differences in commercial financial statements and fiscal financial statements for more efficient then fiscal Financial Statements prepared in tandem with commercial financial statements, meaning that although commercial or business financial statements are prepared on the basis of business accounting principles, but the provision of taxation is dominant in the process of reporting the preparation of reports finance. The causes of differences in commercial financial statements and fiscal financial statements are due to differences in accounting principles, accounting methods and procedures, differences in income and expense recognition, as well as differences in income and expense treatment.. In addressing the differences that occur between the Commercial Income Statement and the Fiscal Income Statement, based on the Financial Accounting Standards and the applicable tax law, based on the results of research and calculation analysis of the calculation of fiscal reconciliation to the Financial Statement of profit